Effectiveness of an integrated nutrition and sanitation education on community health cadres' knowledge and attitudes: A quasi-experimental study - Akifa Syahrir; Lely Lusmilasari; Fitri Haryanti; Nur Hijrah Tiala; Cindy Puspita Sari Haji Jafar; Sri Resky Mustafa; Agustini Liviana Dwi Rahmawati (Journal of Public Health and Development, 2026)
Stunting continues to represent a critical public health concern in Indonesia, with community health cadres playing a pivotal role in preventive efforts at the grassroots level. Despite this, empirical evidence evaluating integrated training approaches combining nutrition education with sanitation-based approaches remains limited. This study aimed to evaluate the effectiveness of the Integrated Stunting Prevention Education (SIDUCETING) program in improving the knowledge and attitudes of community health cadres. A quasi-experimental study with non-equivalent control groups was conducted from June to September 2019. A total of 63 cadres participated in the study, comprising an intervention group (n=32), and a control group (n=31). The intervention group consisted of a two-day SIDUCETING training program integrating nutrition-specific education with Community-Based Total Sanitation (STBM) principles, emphasizing experiential learning through practical demonstrations and hands-on skill development. Cadre’s knowledge was measured using a 20-item questionnaire, while attitudes were assessed using a 15-item Likert-scale instrument at baseline and immediately following post-intervention. Data were analyzed using the Mann-Whitney U test and the Wilcoxon signed-rank test. Baseline assessments indicated no significant differences between groups in knowledge (p=0.357) or attitude scores (p=0.985). Post-intervention, the intervention group demonstrated significant improvements in both knowledge (median: 10 to 18, p